Emission, absorption and propagation of acoustic THz-Waves in solids - EISENMENGER, W. (Archives of Acoustics, 1979)
Recent experimental developments in generation and detection of THz acoustical phonons have led to studies of phonon emission, propagation and absorption in solids. New results of this acoustical phonon spectroscopy concern phonon interactions with collective excitations (phonons, photons, magnons), localized excitations (resonant scattering of impurities, radiationless transitions) and electronic excitations in metals, superconductors and semiconductors. The different experimental methods and their applications to phonon interaction studies are discussed.